Performance Characterization of Load Balancing Algorithm - Krishan, R. (Journal of Scientific Research, 2021)
The developing interest in mobile services increases the demand for well-planned and cautiously managed wireless local area networks (WLAN) deployment. In WLAN, a station can access services of the network through an access point (AP) after associating with it. Any number of access points can be accessed by the station whose signal strength is available from among the APs. But practically, a WLAN station (STA) always associates with the access point with higher signal strength among the APs. In WLAN, mobile stations continuously change their location, which results in an uneven network load allocation. This uneven load dissemination prompts an extensive performance degradation of WLAN. This paper presents mathematical modeling to characterize the WLAN performance by balancing the network load and enhancing network throughput. Riverbed Modeler simulator was used to investigate the performance parameters as network load and throughput of the network.